Kajian Experiment Penggunaan Agregat Kasar Pada Campuran Aspal Dingin Cold Mix Lastbutag AC-WC - Suaib Syaifullah; Adnan Adnan; Hendro Widarto (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Cold mix asphalt mix lastbutag wear layer can improve road pavement, controlling the quality of road construction work from each stage of activity is very necessary to control the quality of road work, because the success of road work cannot be separated from the quality of the work results. This research aims to determine the characteristics and influence of aggregates on cold mix asphalt lastbutag wear layers. This research method uses experimental methods at the Road and Asphalt Laboratory, Faculty of Engineering, Muhammadiyah University, Parepare, in August-September 2023. The results of the visualization analysis show that the stability of 4.5% asphalt is 1345.95 kg, VMA of 6.5% asphalt is 17.69%, VIM of asphalt 4.5% was 6.59%, 6.5% VFB asphalt was 77.99%, 6.5% asphalt flow was 3.99 mm, 5% asphalt MQ was 718.06 mm/kg. The characteristic values obtained through marshall testing with the optimum asphalt content results obtained were 5.275%, and the use of aggregate in the AC-WC Lastbutag Cold Mix Asphalt Mix has met the 2018 General Bina Marga Specifications and is suitable for use in AC-WC asphalt concrete mixtures.